Bacteriology of the burn wound at the Bai Jerbai Wadia Hospital for children, Mumbai, India-A 13-year study, Part I-Bacteriological profile - Srinivasan Shankar; Vartak Arvind; Patil Aakanksha; Saldanha Jovita (Indian Journal of Plastic Surgery)
Aim: To study which organisms were prevalent in our burn unit and their antibiotic sensitivity pattern in brief. Method: Microbiological data of 1534 patients admitted to the burns unit of the Bai Jerbai Wadia Hospital for Children, Mumbai over a period of 13 years (1994-2006) was reviewed retrospectively. A total of 9333 swabs were cultured and antibiotic sensitivities to the isolated organisms determined. The age group of patients admitted to our facility ranged from one month to 15 years. Result: Klebsiella was the predominant organism in our set-up (33.91%), closely followed by Pseudomonas (31.84%). The antibiotic sensitivities of the isolated organisms are discussed in detail in the text. Conclusion: Every treatment facility has microorganisms unique to it and these change with time. It is therefore of paramount importance to have an in-depth knowledge of the resident organisms and their antibiotic sensitivity pattern so that infection-related morbidity and mortality are improved.